Alcune questioni di analisi numerica - C.I.M.E. Summer School Perugia, Italy) (1964; Ghizzetti, Aldo.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2010)
A. Ghizzetti: a) Lezioni sui procedimenti di quasilinearizzazione e applicazioni. b) Nozioni fondamentali sulle equazioni alle differenze e sulle frazioni continue.- P. Wynn: Four lectures on the numerical application of continued fractions.- W. Gautschi: Strength and weakness of three-term recurrence relation.- F.L. Bauer: Use of continued fractions and algorithms related to them.
A. Ghizzetti: a) Lezioni sui procedimenti di quasilinearizzazione e applicazioni. b) Nozioni fondamentali sulle equazioni alle differenze e sulle frazioni continue -- P. Wynn: Four lectures on the numerical application of continued fractions -- W. Gautschi: Strength and weakness of three-term recurrence relation -- F.L. Bauer: Use of continued fractions and algorithms related to them.
"Lectures given at a Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.), held in Perugia, Italy, September 7-16, 1964."
Electronic reproduction.
Text in Italian and English.
Keywords: Numerical analysis -- Congresses; Electronic books